Attitudes to Arms Control, Australia, February 1985 (ADA Dataverse, 2018)
Topics in this survey include: confidence in the ability of the US and USSR to deal responsibly with world problems; commitment by US and USSR to reach arms reduction agreement; respondents reading on Jan. 1985 arms reduction talks; likelihood of effectiveness of arms control negotiations; likely time period before arms control agreements reached; arms control verification procedures; respondent's reading on SDI or 'Star Wars'; consequences of US development of anti-missile defence system; anti-missile defence system and deterrence v./ 'bargaining chip'. Standard variables include household size, age, marital status, schooling, occupation of respondent or of main income earner, religion, House of Representatives Federal Vote, household income, sex, area, size of community. This study is part of a series (SSDA No's 525 to 532) commissioned by the United States Information Service between 1982 and 1985 on Australians' attitudes to defence issues. Similar studies were carried out in New Zealand at the same time (SSDA No's 521 to 524) which contain some parallel questions.